N-myc-interactor mediates microbiome induced epithelial to mesenchymal transition and is associated with chronic lung allograft dysfunction - Banday, Mudassir M.; Kumar, Archit; Vestal, Grant; Sethi, Jaskaran; Patel, Kapil N.; O'Neill, Edward B.; Finan, Jon; Cheng, Feng; Lin, Muling; Davis, Nicole M.; Goldberg, Hilary; Coppolino, Antonio; et al. (The Journal of heart and lung transplantation, 2021)
Recent evidence suggests a role for lung microbiome in occurrence of chronic lung allograft dysfunction (CLAD). However, the mechanisms linking the microbiome to CLAD are poorly delineated. We investigated a possible mechanism involved in microbial modulation of mucosal response leading to CLAD with the hypothesis that a Proteobacteria dominant lung microbiome would inhibit N-myc-interactor (NMI) expression and induce epithelial to mesenchymal transition (EMT). Explant CLAD, non-CLAD, and healthy nontransplant lung tissue were collected, as well as bronchoalveolar lavage from 14 CLAD and matched non-CLAD subjects, which were followed by 16S rRNA amplicon sequencing and quantitative polymerase chain reaction (PCR) analysis. Pseudomonas aeruginosa (PsA) or PsA-lipopolysaccharide was cocultured with primary human bronchial epithelial cells (PBEC). Western blot analysis and quantitative reverse transcription (qRT) PCR was performed to evaluate NMI expression and EMT in explants and in PsA-exposed PBECs. These experiments were repeated after siRNA silencing and upregulation (plasmid vector) of EMT regulator NMI. 16S rRNA amplicon analyses revealed that CLAD patients have a higher abundance of phyla Proteobacteria and reduced abundance of the phyla Bacteroidetes. At the genera level, CLAD subjects had an increased abundance of genera Pseudomonas and reduced Prevotella. Human CLAD airway cells showed a downregulation of the N-myc-interactor gene and presence of EMT. Furthermore, exposure of human primary bronchial epithelial cells to PsA resulted in downregulation of NMI and induction of an EMT phenotype while NMI upregulation resulted in attenuation of this PsA-induced EMT response. CLAD is associated with increased bacterial biomass and a Proteobacteria enriched airway microbiome and EMT. Proteobacteria such as PsA induces EMT in human bronchial epithelial cells via NMI, demonstrating a newly uncovered mechanism by which the microbiome induces cellular metaplasia.